2017
DOI: 10.1124/mol.116.107904
|View full text |Cite|
|
Sign up to set email alerts
|

The Orphan Receptor GPR17 Is Unresponsive to Uracil Nucleotides and Cysteinyl Leukotrienes

Abstract: Pairing orphan G protein–coupled receptors (GPCRs) with their cognate endogenous ligands is expected to have a major impact on our understanding of GPCR biology. It follows that the reproducibility of orphan receptor ligand pairs should be of fundamental importance to guide meaningful investigations into the pharmacology and function of individual receptors. GPR17 is an orphan receptor characterized by some as a dualistic uracil nucleotide/cysteinyl leukotriene receptor and by others as inactive toward these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…Inadvertent upregulation of 15,44 The recent identification of synthetic GPR18 ligands should allow resolution of authentic ligand specificity, as has been the case for other controversial GPCRs. 45,46 We observed evidence of weak activation of yeast expressing CB 2 by…”
Section: Thosementioning
confidence: 94%
“…Inadvertent upregulation of 15,44 The recent identification of synthetic GPR18 ligands should allow resolution of authentic ligand specificity, as has been the case for other controversial GPCRs. 45,46 We observed evidence of weak activation of yeast expressing CB 2 by…”
Section: Thosementioning
confidence: 94%
“…Similar results were obtained with CDS, another label-free technique, which translates intracellular signaling events into bioimpedance signals. 15 , 16 , 18 , 25 , 26 Therein, activation of GIRK1/2 with ML297 led to characteristic noninverting and concentration-dependent negative signals with similar steady kinetics over 3600 s in a strictly GIRK-dependent manner ( Figure 1 f,g). Control stimulus ATP was equally effective in both cell lines again confirming that ML297 recordings were no consequence of generally enhanced responsiveness in GIRK-expressing cells ( Figure 1 h).…”
Section: Resultsmentioning
confidence: 89%
“…After 6 weeks of differentiation, terminally differentiated oligodendrocytes, which displayed a more complex morphology and expressed the mature myelin marker MBP, revealed diminished GPR17 expression (Figure 1E). To investigate whether activation of GPR17 prevents maturation of human oligodendrocytes, we differentiated the oligodendrocyte cultures in the presence or absence of the small-molecule GPR17 agonist MDL (Hennen et al, 2013; Simon et al, 2017). Immunocytochemical analyses showed that cells expressing the oligodendrocyte marker O4 were also immunopositive for MBP under control conditions, thus corroborating the capacity for myelin expression in our hiPSC-derived oligodendrocyte culture (Figure 1G).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the absence of primary endogenous messengers for GPR17, synthetic ligands have become available and have aided in defining the biological function of this receptor. MDL29,951 (MDL), a small-molecule surrogate agonist, and pranlukast, an anti-asthma medicine and cysteinyl-leukotriene 1 receptor blocker, activate and inhibit GPR17, respectively, both in heterologous cell expression systems and in primary rodent oligodendrocyte cultures (Hennen et al, 2013; Simon et al, 2016, 2017). Stimulation with MDL arrests primary wild-type, but not GPR17-deficient, mouse oligodendrocytes at a less differentiated stage, resulting in a pronounced loss of myelin basic protein (MBP)-positive cells (Hennen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%